The Historiography of the Research of Scientific, Educational and Managerial Activity of Vasyl Karazin (the Late ХІХ Century – the 1920th) - Maistruk, Olha (Pedagogical Discourse, 2013)
Historiographical analysis of the research concerning scientific, educational and managerial activity of Vasily Karazin was made in the article. The necessity of historiographical research in the history of pedagogy, including a study of the pedagogical personalities was determined. Periodization of the scientific, educational and administrative activities of the scientist was also done. However, for a deeper clarification of the role and value of creative heritage of V.Karazin the author analyzed the first stage of the creative activity of the educator. The actual material of biographical works of V.Karazin has still had a great value for the creation of the biography of the scientist from the standpoint of modernity and scientific research of his many-sided activities. It was determined that the research of his heritage as a public and political statesman was fully disclosed. However scientific and educational heritage of V.Karazin was studied partially, his contribution to Ukrainian education is under estimated.